The safety parameters of the study on intraductal cytotoxic agent delivery to the breast before mastectomy - Zhang, Bailin; Love, Susan M.; Chen, Guoji; Wang, Jing; Gao, Jidong; Xu, Xiaozhou; Wang, Zhongzhao; Wang, Xiang (Chinese Journal of Cancer Research, 2014)
Background: Intraductal administration of cytotoxic agents has been shown to inhibit the development of breast cancer in animal models. The object of this study was to demonstrate the safety of intraductal delivery cytotoxic agents in patients prior to mastectomy. This method is hopeful to be developed as a chemoprevention approach in patients with pre-malignant or non-invasive ductal lesions to prevent breast cancer which will be further developed. Methods: Two drugs, pegylated liposomal doxorubicin (PLD) and carboplatin were administered at three dose levels (PLD: 10, 20, 50 mg and carboplatin 60, 120, 300 mg). There were five subjects in each group with 15 subjects treated with each drug once. Venous blood samples were obtained for pharmacokinetic analysis. The breast was removed surgically 2-5 days post administration and the treated ducts were marked to enable identification on pathological evaluation. Results: Intraductal administration was generally well-tolerated with mild, transient breast discomfort. In the carboplatin arm, three women at the 300 mg dose experienced mild nausea and vomiting. In the PLD arm most women had mild erythema and swelling of the breast over the 72 hours following the drug administration. Patients receiving the 50 mg dose experienced local erythema until the time of surgery. Pharmacokinetic analysis showed that carboplatin rapidly entered systemic circulation with an early peak time (Tmax ~30 min) with a corresponding plasma ultrafiltrate area under the curve (AUC) consistent with the Calvert Formula using estimated glomerular filtration rate (GFR). Total plasma doxorubicin had delayed peak concentration times (Tmax >48 hours) with a linear dose response and peak concentrations substantially lower than expected from equivalent intravenous injection dosing. No doxorubicinol metabolite was detected in the plasma. Conclusions: This study demonstrates that cytotoxic drugs can be safely administered into breast ducts with minimal toxicity.